City memory and saptial imagination in the Mahua fiction (1950-2003) - Lim, Chia Yen (2021)
“City” is an important subject in the writing of Mahua fiction, literally means Malaysian Literature in Chinese language. “City” first appeared in the colonial era which emphasized the export mode of economic development. Since the independence of Malaya, the nation experienced three stages of city development, that is post-colonial period (1950-1970), Bumiputraismnew policies period and beyond (1971-1980), and the era of Barisan Nasional-Mahathir regime (1981-2003). From the perspective of postcolonialism and the concept of modern space, this research tries to analyze how the Mahua authors portrayed the three stages mentioned above in their writing. The first part of this research explored how Mahua fiction (re)present the new emergent city in the colonial and post-colonial era. The second part tried to review the bumiputraism-new policies implemented by the government in the 1970s, as well as the emergence of modernization and the cityscape portrayed in the fiction, by applying the concept of political space which was proposed by Henri Lefebvre. Besides that, narrative of city image and the sense of place proposed by Kevin Lynch and Yi-Fu Tuan respectively will be applied in order to examine the writing juxtaposed to the transformation of urban space due to the modernization-industrialization process during the BN-Mahathir Regime, the transnational and trans-city movement of the Chinese youth, and the city as a platform for the masses to bring about social reform. Social issues in post-colonial period and Bumiputraism-new policies period were mostly discussed in their realism writings whereas the contents in the era of Mahathir regime emphasized historical and political issues in the city space. City metaphor writings which was well presented also appeard in this period.